Ethnographic worldviews transformations and social justice - Barbour, Karen N.; Pope, Clive C.; Rinehart, Robert E. (Springer Netherlands Imprint: Springer, 2014)
This book discusses ethnography from the three points of view of Emerging Methodologies, Practice and Advocacy, and Social Justice and Transformation, with an over arching emphasis on researchers' and participants' worldviews. While these three thematic threads cut across each other, the actual chapters will be located so that the reader understands many of the current issues and concerns-with specific exemplars from around the globe-for ethnographers. 'Ethnographic Worldviews: Transformations and Social Justice' will have its "finger on the pulse" of contemporary ethnography. Chapters demonstrate up-to-the-moment awareness of ethnographic methods, concerns, and subject matters within contemporary ethnographic writing. Authors are deeply engaged in both their subject matter and their method. Unlike other ethnographic books which often suggest "giving voice to others", this book will actually give voice to a wide variety of perspectives, from the points of view of researchers